Principal's Leadership in Forming Student Discipline - Nasution, Wahyu Ardian; Siahaan, Amiruddin; Hasibuan, Badoar (STAI Publisistik Thawalib Jakarta, 2025)
The principal's leadership is key in achieving the school's vision, mission, and goals through well-planned and gradual programs. This study examines the principal's role in shaping student discipline at Bina Siswa Private Middle School. The research method used is a case study approach with data collection techniques through observation, interviews, and documentation. The results: the principal plays a crucial role in shaping student discipline by establishing and enforcing rules that promote positive behaviour and prevent negative actions, creating a conducive learning environment. As a leader, the principal sets an example by being punctual and organising programs to improve student behaviour, such as extracurricular activities and character-building initiatives. As a supervisor, the principal conducts classroom observations and home visits to ensure consistent discipline and monitor student development. Internal and external factors influence student discipline, including family, school, and the community. Although discipline fosters a productive environment, excessive strictness may cause stress, requiring a personalized educational approach. In conclusion, the principal's leadership is vital in shaping the discipline character at school.